2020
DOI: 10.1177/1045389x20969911
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance creep and recovery behavior of magnetorheological elastomers

Abstract: As a novel conductive elastomer, magnetorheological elastomers (MREs) featuring both high sensitivity and wide working range have been employed as a new sensing material for flexible tactile sensors. Their sensing mechanism, that is, the spatial distribution rearrangement of particles under compression, completely differs from their conventional counterparts. The piezo-capacitive effect of MREs resulting from the unique mechanism of particles rearrangement is actually a response to the microscopic mechanical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The rule of polymer resistance creep is depicted in Figure 4 b, and a comparison with Figure 4 a demonstrates that the resistance creep process is remarkably similar to the strain creep process [ 12 , 25 ]. This suggests that, in the research of creep, evaluating the creep properties of materials by strain has the same effect as evaluating the creep characteristics of materials using electrical indicators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rule of polymer resistance creep is depicted in Figure 4 b, and a comparison with Figure 4 a demonstrates that the resistance creep process is remarkably similar to the strain creep process [ 12 , 25 ]. This suggests that, in the research of creep, evaluating the creep properties of materials by strain has the same effect as evaluating the creep characteristics of materials using electrical indicators.…”
Section: Resultsmentioning
confidence: 99%
“…The recent nanocomposite study demonstrated that the volume percentage of particles, particle size, the ratio of silicone rubber to silicone oil, the amount of applied pressure, the pressure holding time, and temperature, among others, are the primary factors influencing creep. Fan et al [ 12 ] examined the impacts of particle volume fraction, particle size, etc., on sensor creep and determined that the resistance to sensor creep reduces as the number of contributing factors other than particle size increases. Ayesha Naz et al [ 13 ] investigated the effect of the hydrothermal reduction of graphene oxide (RGO) on the creep of polypropylene matrix and concluded that polymer nanocomposites generated by high-temperature polymerization can significantly improve creep resistance; at the same time, the effect of carbon nanotubes and graphene polymers on creep under the same matrix was also investigated separately, and the comparison revealed that graphene has better creep resistance than carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%